Effects of Music and Choice Listening on Arousal Changes. - Miller, Katie; Brazeau, Christina; Fuiten, Melissa; Woelfel, Jessica (My University, 2008)
This study based its method on Pitzen and Rauscher’s 1998 study, testing 60 participants between classical stimulative, sedative, or no music conditions and choice or no choice exposure conditions. We calculated results using two 2 X 3 design (Condition X Music) completely randomized factorial analyses of variance for mean difference of heart-rate (HR) before and after the exposure condition and for state anxiety, a short-term form of anxiety. Findings indicated that mean HR difference increased in the no choice condition compared to the choice. Participants scored significantly higher state anxiety for choice-stimulative as compared to the no choice-stimulative condition. Additionally, participants in the no choice-no music condition showed significantly higher state anxiety compared to those in the no choice-stimulative condition. For future research, experimenters may include the skin conductive measure galvanic skin response (GSR) as a second dependent variable. Finally, participants could wait 5 to 10 min in order to acclimate to the testing environment.
Oshkosh Scholar, Volume 3, 2008 pp. 73-81
Keywords: Music--Physiological effect